Posouzení informačního systému firmy a návrh změn - Petrová, Pavla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Tato diplomová práce se zabývá problematikou informačních systémů v podnikovém prostředí. Praktická část je zaměřena na posouzení současného řešení IS/IT ve zvoleném hotelu pomocí analýzy HOS 8 a ZEFIS. Na základě těchto analýz je v poslední části práce navrhnut soubor řešení pro zlepšení stávajícího stavu informačního systému a to z hlediska jak vyváženosti, tak i efektivnosti.

This dissertation is dealing with the issue of information systems in business environment. The practical part focusses on examining the contemporary solutions IS/IT at a chosen hotel with the help of analysis HOS 8 and ZEFIS. Based on these analyses the final part of this thesis proposes solutions for the improvement of the current state of IS from balance perspective as well as efficiency.
Information System Assessment and Proposal for ICT Modification
Keywords: Informační systém; informace; data; životní cyklus IS; COBIT; ITIL; HOS 8; efektivnost IS; Cloud computing.; Information system; information; data; IS life cycle; COBIT; ITIL; HOS 8; IS efficiency; Cloud computing.